(untitled) (Journal of Engineering, 2023)
Recently, a great rise in the population and fast manufacturing processes were noticed. These processes release significant magnitudes of waste. These wastes occupied a notable ground region, generating big issues for the earth and the environment. To enhance the geotechnical properties of fine-grained soil, a sequence of research projects in the lab were conducted to analyze the impacts of adding sludge waste (SW). The tests were done on both natural and mixed soil with SW at various proportions (2%, 4%, 6%, 8%, and 10%) based on the dry mass of the soil used. The experiments conducted focused on consistency, compaction, and shear strength. With the addition of 10% of SW, the values of LL and PI decreased by 29.7% and 38.5%, respectively. Also, with 10% of SW, the values of swelling percent (SP) and swelling pressure (SPR) decreased by 34% and 33%. On the other hand, SW content increase led to the rise in unconfined compressive strength (UCS) of the soil tested from 511kPa to 726kPa with the addition of 10% SW. Based on the findings, it can be confirmed that 10% SW in its natural state is notable for improving fine-grained soil strength and reducing the environmental hazard related to this waste type.